Calibration of digital camera for medical photogrammetry - Ahmad, Anuar (2004)
Today, there are several low cost softwares that are available in the market that could be used for digital close range photogrammetry applications such as for medical photogrammetry. Most softwares could be used to calibrate digital camera or other sensors and produce accurate results. This paper discusses about the experience of calibrating a consumer digital camera using low cost digital close range photogrammetric software. A test field was used to calibrate the digital cameras. Convergent images and retro-reflective targets were employed in the study. The process of photography and processing the photographs were carried out within short period of time. In this study, self-calibrating bundle adjustment embedded in the software was used to recover the camera calibration parameters of the consumer digital camera. Subsequently, the consumer digital camera was used to capture the photographs of human face for medical photogrammetry application. Output of calibrating the digital cameras include exterior orientation parameters, camera calibration parameters and the object space coordinates. The results showed that all the camera calibration parameters could be recovered without any difficulties and could be used to capture photographs or data for medical photogrammetry applications. Also the results from this study suggest that consumer digital camera is potential to be used in many close range photogrammetric applications and when the budget is limited.